Performance of SMEs: A Special Focus on Small Size Businesses (SSBs) Determinants of Growth at the Tangail Using Logistic Regression (Global Journal of Human-Social Science, 2020)
Small scale enterprises (SMEs) take possession of dominant position in any developing countries like Bangladesh. Small scale enterprises (SMEs) specially focused on the study of Small scale business (SSBs) at tangail which is significant contribution of countries economy where density of population is very high because it offers large number of employment generation opportunities and income generation at low cost which is reduction poverty. Considering the importance this study has strived to identify those were collecting primary data which is statistically significant. First using educational level of entrepreneur's, loan facilities,' sector of loan collecting, employment generation and poverty reduction analyze frequency of statistics and later using logistic regression determinant of gross profits, asset growth at tangail district. The study shows that entrepreneurs of SSBs 82% influences of profit rising by educational levels and ownership of business is 58% and 72% profits rising when loan facilities of SSBs.
Keywords: SME; small size of businesses (SSBs); poverty reduction; logistic regression; predictors2019; growth